2004
DOI: 10.1159/000081110
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific Allometry of the Brain and Brain Regions in Parrots (Psittaciformes): Comparisons with Other Birds and Primates

Abstract: Despite significant progress in understanding the evolution of the mammalian brain, relatively little is known of the patterns of evolutionary change in the avian brain. In particular, statements regarding which avian taxa have relatively larger brains and brain regions are based on small sample sizes and statistical analyses are generally lacking. We tested whether psittaciforms (parrots, cockatoos and lorikeets) have larger brains and forebrains than other birds using both conventional and phylogenetically b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
151
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(156 citation statements)
references
References 166 publications
4
151
1
Order By: Relevance
“…Both parrots and primates have similar relative brain volumes (Iwaniuk et al 2005), are long-lived (Austad and Fischer 1992, Munshi-South and Wilkinson 2006, Young et al 2012, have extended developmental periods Nelson 2003, Emery 2006), live in complex social groups (Dunbar andShultz 2007, Hobson et al 2013), and show evidence of advanced cognition (Iwaniuk et al 2005, Roth andDicke 2005). Parrots also share additional characteristics with humans, which display the highest social and cognitive complexity of any species (Wilson 1975, Herrmann et al 2007.…”
Section: Exchange Of Foraging Informationmentioning
confidence: 99%
“…Both parrots and primates have similar relative brain volumes (Iwaniuk et al 2005), are long-lived (Austad and Fischer 1992, Munshi-South and Wilkinson 2006, Young et al 2012, have extended developmental periods Nelson 2003, Emery 2006), live in complex social groups (Dunbar andShultz 2007, Hobson et al 2013), and show evidence of advanced cognition (Iwaniuk et al 2005, Roth andDicke 2005). Parrots also share additional characteristics with humans, which display the highest social and cognitive complexity of any species (Wilson 1975, Herrmann et al 2007.…”
Section: Exchange Of Foraging Informationmentioning
confidence: 99%
“…1). Notably, even in a serial-sectioned brain, the boundaries of brain regions are difficult to delineate in some specimens (Boire & Baron, 1994;Iwaniuk et al 2005), and our definition was based on the appearance of the brain endocast. Hence, our definition of regional boundaries does not completely coincide with that of histological boundaries.…”
Section: Geometric Morphometricsmentioning
confidence: 99%
“…Hence, it is known that the brain with a larger telencephalon is highly encephalized (Iwaniuk et al 2005), a large telencephalon correlates with an increase in relative brain volume. Iwaniuk et al (2005) reported that psittaciforms and passerines whose telencephalon is significantly larger than that of other birds have a relatively smaller mesencephalon, optic tectum, cerebellum and myelencephalon than non-passerines. We clarified that the apparent size of the brain regions changes according to the degree of encephalization, and this finding corroborates the volumetric result of Iwaniuk et al (2005).…”
Section: Size-independent Changementioning
confidence: 99%
See 1 more Smart Citation
“…As foraging innovation frequency has been linked with larger relative brain size [5,7,35,36], we investigated agerelated differences in innovative problem-solving abilities in a large-brained parrot species [37], the forest-dwelling kaka (Nestor meridionalis). Kaka are an especially interesting species for studying the effects of personality and ecology on innovative problem-solving skills as they are generalist, extractive foragers [38], characteristics thought to be associated with increased problem-solving success [39,40].…”
Section: Introductionmentioning
confidence: 99%